THE IMPACT OF RELIGIOSITY ON THE MORALITY OF ISLAMIC EDUCATION STUDENTS - Falikah, Tri Yaumil; Nuryana, Zalik; Yuliana, Anaas Tri Ridlo Dina; Malik, Shazia (Graduate School of Universitas Negeri Malang, 2024)
Religiosity is an important aspect in shaping student morale, especially for Islamic Education (IE) students who are future educators. The purpose of the study was to look for the influence of religiosity on the morale of Islamic Religious Education students at Universitas Ahmad Dahlan. This research is a quantitative study with the population of IE students from 2019 to 2021 amounting to 699 students. The technique of taking sample uses the Slovin formula, namely as many as 90 students who were taken randomly (random sampling). The primary data collection tool used is a 4-scale Likert scale questionnaire. The instruments were tested using validity tests as well as reliability tests. The instruments were also tested for classical assumptions with normality and reliability tests. The primary data were then analyzed by simple linear regression statistical techniques. The results showed that the level of religiosity of IE students was in the high category, it was proven that from 90 respondents, there were 81 respondents (90%) showing a high and very high level of religiosity, while the remaining 9 respondents (10%) were in the low and medium categories. Then for the moral level of IE students, it is in the moderate category. This is shown by 90 respondents, 21 respondents (23.3%) belonged to the high category, 47 respondents (52.2%) were classified as moderate, and 22 respondents (24.4%) were classified as low. The results of the analysis showed that there was an influence of religiosity on the morale of IE students as evidenced by the value of the coefficient of determination (R Square) of 0.469, which contained the understanding that the influence of the free variable (Religiosity) on the bound variable (Moral) was 46.9%. This means that the higher the level of religiosity possessed by students, the higher their morale, and vice versa.